MOLT RELATED BIOCHEMICAL CHANGES IN FRESHWATER PRAWN, MACROBRACHIUM MALCOLMSONII (H. MILNE EDWARDS) - Paramaraj Balamurugan; Pitchaimuthu Mariappan; Chellam Balasundaram (Tropical Life Sciences Research, 2006)
Biochemical changes which occur during the molt cycle of freshwater prawn, Macrobrachium malcolmsonii and the characteristic features of the five molt stages from A to E are described in this article. In abdominal muscle, the carbohydrate level decreased significantly (P < 0.05) from 18.38 ± 0.91 mg/g in stage A to 17.56 ± 0.53 mg/g in stage B, and then increased significantly (P < 0.05) to 20.68 ± 0.74 mg/g in stage D. Though, the maximum protein level was recorded in stage D (71.6 ± 1.89 mg/g) and the minimum level was noticed in stage B (56.51 ± 1.29 mg/g) (P < 0.05). The lipid level reflected the same trend with the maximum in stage D (75.44 ± 0.72 mg/g) and the minimum in stage B (54.88 ± 0.25 mg/g) (P < 0.05). The total mineral content of the muscle was at the maximum level in stage C (65%) and the minimum in stage E (23%) (P < 0.05). Of the three minerals, in muscle and exuvium, the calcium level (17.4%) is always higher than in the latter. Meanwhile between all the molt stages, the amount of potassium and sodium is higher in stage D. Variation in the moisture content reported in the study is due to the accumulation of organic materials. Similarly, increased ash content from stage A (4.5 ± 0.5%) to stage E (11.8 ± 1.2%) (P < 0.05) is also due to the outcome of mineral accumulation.